Modelling developmental changes in repeated-sprint ability by chronological and skeletal ages in young soccer players - Valente-dos-Santos, J.; Coelho e Silva, M. J.; Martins, R. A.; Figueiredo, A. J.; Cyrino, E. S.; Sherar, L. B.; Vaeyens, R.; Huijgen, B.C. H.; Elferink-Gemser, M. T.; Malina, R. M. (International Journal of Sports Medicine, 2012)
This study investigated the influence of chronological (CA) and skeletal ages (SA), anthropometry, aerobic endurance and lower limb explosive strength on developmental changes in repeated-sprint ability (RSA) in soccer players aged 11-17 years. Participants were annually followed over 5 years, resulting in 366 measurements. Multilevel regression modelling analysed longitudinal data aligned by CA and SA (Model 1 and 2, respectively). After diagnosing for multicollinearity, it was possible to predict RSA with 2-level hierarchical models [Model 1 (CA as Level 2 predictor): Log-Likelihood=1 515.29, p<0.01; Model 2 (SA as Level 2 predictor): Log-Likelihood=1 513.89, p<0.01]. Estimating sum of sprints for young soccer players are given by equations: sum of sprints=84.47 - 1.82×CA + 0.03×CA2 - 0.05×aerobic endurance - 0.10×lower limb explosive strength - 0.09×fat-free mass + 0.13×fat mass (Model 1); 73.58 - 0.43×SA - 0.05×aerobic endurance - 0.10×lower limb explosive strength - 0.08×fat-free mass - 0.45×training experience + 0.13×fat mass (Model 2). The models produced performance curves that may be used to estimate individual performance across adolescent years. Finally, the validity of each model was confirmed based on corresponding measurements taken on an independent cross-sectional sample.